The Influence of Intellectual Capital on Firm Value through Financial Performance as an Intervening Variable (Study on Pharmaceutical Sub-Sector Companies Listed on the Indonesia Stock Exchange Periode 2016 - 2019) - Wulandari, Afiani; Purbawati, Dinalestari (Jurnal Ilmu Administrasi Bisnis, 2021)
The formation of a company is due to the objectives to be achieved, one of which is maximizing company value. Firm value is a reflection of the company's performance which is formed by supply and demand in the capital market which can be influenced by several factors, including intellectual capital and financial performance. This study aims to examine the effect of intellectual capital on firm value through financial performance as an intervening variable in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2016 – 2019. The data used is secondary data derived from the publication of financial reports by the IDX. The analysis method used is regression analysis and single test. The results showed that simultaneously intellectual capital and financial performance had a significant effect on company value, partially intellectual capital had no effect on company value, intellectual capital had no effect on financial performance, financial performance had no effect on firm value, and financial performance was not an intervening variable between intellectuals. capital and financial performance. It is recommended that pharmaceutical companies optimize their intellectual capital and financial performance so as to increase company value to convince investors. Investors are advised before placing their funds to consider intellectual capital, financial performance and other external factors that may affect company value.